The Effect of Sport Enjoyment, Physical Activity, and Physical Fitness on the Academic Achievement of Elementary School Students in Malang Regency - Ari Yudianto; Susilo Bekti; Ahmad Lani (Badan Penerbit STIEPARI Press, 2025)
Academic achievement reflects the quality of human resources. With high academic performance, it is hoped that the country can produce a smart and competitive young generation in the global era. Sport enjoyment in the PJOK subject is an important factor in increasing active participation among elementary school students. Game-based physical activities not only encourage students to move actively but also help develop important components of physical fitness. This research aims to investigate the direct and indirect impact of sport enjoyment, physical activity levels, and physical fitness on students' academic achievement. This quantitative research uses a multivariate path analysis design involving 194 elementary school students in Malang Regency. Data collection was conducted using two standardized instruments: the Physical Activity Enjoyment Scale and the Physical Activity Questionnaire for Children, as well as through direct measurement of physical fitness using the Indonesian Student Fitness Test. Research results indicate that the excitement of exercising has a significant impact on the physical activity levels of students. Excitement and levels of physical activity also positively influence physical fitness. The excitement in exercising has been proven to have a positive influence both directly and indirectly on academic achievement through physical fitness. This finding emphasizes the importance of developing enjoyable physical activities in PJOK learning to support students' physical development and academic achievement. Teachers are advised to apply game-based learning methods to maintain student participation and foster healthy lifelong habits.